Rola innowacji w konkurencyjności regionów - Raszkowski, Andrzej (The role of innovation in regions' competitiveness, 2005)
The article presents problems referring to the concept of regions’ competitiveness. The advantages typical for regions of high competitiveness level have been discussed. The problems of innovation system, as one of key factors related to regions’ competitiveness, have been considered. The role of innovation centres in supporting the development based on knowledge has also been emphasized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 54-62